Ambush marketing and rule 40 for Tokyo 2020: A shifting landscape for Olympic athletes and their sponsors - McKelvey, S.; Grady, J.; Moorman, A. M. (Journal of Legal Aspects of Sport, 2021)
This study explores the historical development of the regulatory landscape related to Olympic and Paralympic athlete marketing activities, together with current restrictions imposed on athlete marketing, and discusses potential legal challenges to these restrictions. Specifically, this study analyzed various countries` Rule 40 Tokyo 2020 guidance through a trans-national lens by comparing and contrasting the different approaches found in various national Olympic committees` legal frameworks to combat ambush marketing. The potential legal challenges to the United States Olympic Commititee`s enforcement of new Rule 40 guidance are highlighted, with particular focus on discussing the restrictions and enforcement rights contained within the personal sponsor commitment agreement within the United States for the postponed Tokyo 2020 Games. Critical analysis of the potential impact of enforcing this agreement within the broader Olympic intellectual property and brand protection frameworks for Olympic stakeholders in the US is provided.